The Level of Malondialdehyde in People Exposed to Air Pollution - Aguscik Aguscik; Ridwan Ikob; Sumitro Adi Putra (Intelektual Pustaka Media Utama, 2017)
Air pollution cannot be avoided by people especially those living in big cities. Rubber factories and landfill sites are two examples of activities that can trigger air pollution. H2S gas produced from rubber factories and landfill sites can create unpleasant smells and air contamination and increase free radicals in environment. This study was to assess the level of oxidative stress in people living near rubber factories and landfill sites. This was cross-sectional study involving 60 people as the study sample. The level of H2S gas was measured to determine the presence of air pollution. Blood collected from vena mediana cubiti was drawn to determine the level of malondialdehyde (MDA) as a marker of oxidative stress. Data obtained from this study were analyzed using independent t-test. The levels of H2S gas from landfill site were higher than those from rubber factory (0.482 ppm vs. 0.332 ppm). On the other hand, the average level of MDA in people living near the rubber factory was higher than that living near the landfill site (0.847 ± 0.269 nmol/mL vs 0.748 ± 0.253 nmol/mL). It was found no significant difference (p <0.05) in the average levels of MDA between people living near the rubber factory and those living near the landfill site. There was no significant difference in the average levels of oxidative stress between people living near rubber factory and those living near landfill site.